2021
DOI: 10.1177/17534666211019564
|View full text |Cite
|
Sign up to set email alerts
|

Self-expanding covered metallic stents as a transition to silicone stent implantation in management of severe post-tuberculosis bronchial stenosis

Abstract: Background and aims: Post-tuberculosis bronchial stenosis (PTBS) is one of the most common complications of tracheobronchial tuberculosis. Silicone stent serves as a major treatment for maintaining airway patency. However, silicone stent placement remains a large challenge in patients with severe cicatricial PTBS. Our objective was to evaluate the efficacy and safety of covered, self-expanding, metallic stents (SEMSs) as a transition to silicone stent implantation for treating severe PTBS. Methods: We retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Bronchial scar occlusion caused by bronchial tuberculosis is a serious clinical complication. The commonly used methods for bronchoscopic interventional treatment of bronchial stenosis or occlusion include laser, 14 high‐frequency electrotomy, 15 cryotherapy, 16 balloon dilatation, 17 and stent implantation 18 . But early intervention is still needed for treatment to be effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchial scar occlusion caused by bronchial tuberculosis is a serious clinical complication. The commonly used methods for bronchoscopic interventional treatment of bronchial stenosis or occlusion include laser, 14 high‐frequency electrotomy, 15 cryotherapy, 16 balloon dilatation, 17 and stent implantation 18 . But early intervention is still needed for treatment to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used methods for bronchoscopic interventional treatment of bronchial stenosis or occlusion include laser, 14 high‐frequency electrotomy, 15 cryotherapy, 16 balloon dilatation, 17 and stent implantation. 18 But early intervention is still needed for treatment to be effective. The success rate of common techniques in the later stage is relatively low, and the risk is very high, which is easy to induce massive bleeding and endanger the patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, balloon dilation is the first treatment for PTTS, especially appropriate for annular cicatricial stenosis [ 4 ]. But when this approach fails and many a dilation is required, airway stenting is needed [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…multiple, long segments and poor pulmonary reserves). [4][5] Previous clinical evidences have indicated that silicone stents are a safe and effective treatment for patients with PTTS. [6][7] However, placement of silicone stents needs the auxiliary of rigid bronchoscopy, which promotes the development of self-expanding metallic stents (SEMS).…”
Section: Introductionmentioning
confidence: 99%